ChemInform Abstract: Hierarchical Synthesis of Mo—Sn Oxide Cage‐Bell Hybrid Structures with Superior Lithium Storage. Issue 13 (1st April 2014) - Guo, Hong; Liu, Lixiang; Li, Tingting; Chen, Weiwei; Wang, Yapeng; Wang, Wei
Abstract MoO3‐SnO2@C oxide cage‐bell hybrid nanoparticle aggregates are prepared by a facile Ostwald ripening via solvothermal alcoholysis of SnCl2 and (NH4)6Mo7O24, and sucrose in a mixture of EtOH and glycerol (180 °C, 6‐48 h) followed by drying (60 °C, 12 h) and thermal oxidation (400 °C, 2 h).